ANALISIS KESIAPAN BANK SYARIAH INDONESIA DALAM MENGHADAPI PERKEMBANGAN LAYANAN JASA KEUANGAN BERBASIS TEKNOLOGI INFORMASI - Artiningrum, Nur Zannah (Journal of Financial Economics & Investment, 2022)
The purpose of this thesis research is to determine the readiness and efforts made by BSI in dealing with the development of information technology-based financial services. Informants of this research data were obtained directly from employees of BSI KCP Malang City consisting of Consumer Business Staff, Customer Service, Tellers and also 3 customers from BSI. This type of research uses descriptive qualitative research methods, using data collection techniques such as interview, observation and documentation techniques. The results of this study show that BSI has prepared well in accordance with the Slameto concept, namely physical, mental, emotional loneliness, readiness for needs/motivation of goals, and readiness of skills and knowledge by making efforts, namely training to go digital and increasing human resources.